IMPROVEMENT OF MARKETING ACTIVITY OF BAKERY INDUSTRY ENTERPRISES - ANDRUSHKIV, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article focuses on the issues of improving the marketing activities of bakery enterprises, in particular, analyzed and developed a number of proposals on the example of the structural system of marketing mix "7P". The specific features of bakery products as a commodity are determined, on the basis of which the directions of marketing commodity policy of the bakery enterprise were recommended. A number of principles for building a coordinated system of production and sale of bakery products are proposed. To increase the efficiency of the enterprise in the market of bakery products, it is proposed to create a coordinated system that reflects the flexible interaction of producer and consumer.A model of interaction between producer and consumer in the market of bakery products has been developed, which reflects the mechanism of interaction between producer and consumer in the market of bakery products with the help of a specially created system of distribution channels. The developed model reflects the mechanism of interaction between producer and consumer in the market of bakery products with the help of a specially created system of distribution channels. Where, the main channels of distribution of bakery products are: branded network, urban retail trade network, rural retail trade network and trade and intermediary center.The block diagram of marketing activity management is recommended for the researched bakery enterprises, which will allow to choose the appropriate commodity-market business strategy, which ensures the achievement of the enterprise development strategy. The use of marketing strategies for bakeries should be carried out in the complex in accordance with the recommended block diagram of the management of marketing activities of the enterprise as a whole. It should be noted that the recommended block diagram of marketing management can be used by large bakeries, as its implementation requires a certain resource potential.
Keywords: marketing; marketing activities; product sales; market research; enterprise; marketing management; strategic marketing